FOXP3 gene promoter methylation in endometrial cancer cells - Buchynska, L.G.; Iurchenko, N.P.; Verko, N.P.; Nekrasov, K.A.; Kashuba, V.I. (Experimental Oncology, 2015)
Aim: To determine the methylation level of promoter region of the FOXP3 gene promoter depending on the heterogeneity of intracellular localization of its protein product in endometrial cancer (EC) cells and assess its relation to the clinical and morphological features of tumor. Materials and Methods: Samples of surgical material of 40 EC patients who have not received any specific treatment before the surgery, were studied. Real time methylation-specific PCR (MSP) as well as morphological and immunohistochemical methods were used in the study. Results: Methylation of promoter region of the FOXP3 gene was determined in all EC cases, but variability of the methylation level in EC cells from 45.0% to 85.0% was observed. With tumor progression and in tumors with deep (≥ 1/2) invasion in myometrium, an increase of the methylation level of the FOXP3 and of cell number with cytoplasmic FOXP3 localization was observed. In EC patients the correlation between of methylation level of the FOXP3 gene and the number of FOXP3+ tumor cells with cytoplasmic expression (r = 0.41) was determined. Conclusion: The methylation level of FOXP3 gene promoter region and intracellular localization of its protein product are associated with tumor differentiation grade and the depth of myometrial invasion.